2011
DOI: 10.1017/s0033291711000572
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of object visual processing in body dysmorphic disorder

Abstract: Background Individuals with body dysmorphic disorder may have perceptual distortions for their appearance. Previous studies suggest imbalances in detailed relative to configural/holistic visual processing when viewing faces. No study has investigated the neural correlates of processing non-symptom-related stimuli. The objective of this study was to determine whether individuals with body dysmorphic disorder have abnormal patterns of brain activation when viewing non-face/non-body object stimuli. Methods Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
2
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 64 publications
5
84
2
3
Order By: Relevance
“…Our findings are inconsistent with previous studies that have indicated an excessive reliance on, and processing of, details in BDD (Feusner et al, 2007;Stangier et al, 2008;Feusner et al, 2009;Feusner et al, 2010;Feusner et al, 2011;Jefferies et al, 2012). Although methodological differences limit comparisons across studies on visual processing in BDD, there may be several possible reasons why we did not observe impairments in holistic processing in our patient sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings are inconsistent with previous studies that have indicated an excessive reliance on, and processing of, details in BDD (Feusner et al, 2007;Stangier et al, 2008;Feusner et al, 2009;Feusner et al, 2010;Feusner et al, 2011;Jefferies et al, 2012). Although methodological differences limit comparisons across studies on visual processing in BDD, there may be several possible reasons why we did not observe impairments in holistic processing in our patient sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, using unlimited exposure to images of famous people in the upright and inverted orientation, a second study (Jefferies et al, 2012) found evidence of a superior ability of BDD patients to recognize inverted faces compared to controls. These findings further converge with data from neuroimaging studies in BDD, which have also revealed abnormal brain activations during visual encoding of global elements of faces and houses presented on a screen for 3 or 4 seconds (Feusner et al, 2007;Feusner et al, 2010;Feusner et al, 2011). Taken together, it may be argued that whilst individuals with BDD present intact holistic abilities as evident during short stimulus presentations, longer exposure to stimuli may allow patients enough time to engage in a detailed processing style.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is not entirely surprising given that BDD is associated with executive dysfunction (e.g., difficulties with manipulating, planning and organizing information), attentional biases (Grocholewski, Kliemb, & Heinrichsa, 2012), and visual processing abnormalities. Individuals with BDD tend to encode details rather than holistic or configural aspect of the input from the environment (Feusner, Hembacher, Moller, & Moody, 2011). BDD patients portray some common characteristics of other disorders such as obsessivecompulsive disorder (OCD), anxiety, psychotic, and major depressive disorders.…”
Section: Theoretical and Empirical-based Evidence For Muscle Dysmorphmentioning
confidence: 99%